العالم العربى فى المخيال الغربى : الترجمة والتبادل الثقافى - داود، محمد; الإدريسي، محمد (النادي الأدبي بالرياض, 2018)
It’s a question of showing the importance of image in this study that can convey literature. For this result, translation is imperative in the building a representation of the Other such as it gives to see, from its literature. Arabic language literature has not had the opportunity to be translated into European languages, which reduces its influence, because the European translators of this language have seldom got beyond the framework of One Thousand and one Nights (translated in 1704). So it is necessary to make an effort for the literature produced these last decades by Arabic language writers.
يتعلق الأمر في هذه الدراسة بإبراز أهمية الصورة التي يتضمنها الأدب، وعليه فالترجمة ضرورية في بناء تمثلات الآخر كما يقدم نفسه من خلال أدبه. ولم يحظ في هذا الباب الأدب المكتوب باللغة العربية بالترجمة في اللغات الأوربية. مما جعل الصورة التي تمثل العربي ناقصة؛ بسبب أن المترجمين الغربيين لم يتجاوزوا الإطار المخيالي لـ (ألف ليلة وليلة)، التي ترجمت سنة (١٧٠٤ م) إلا قليلا، وهذا يدفع إلى بذل المزيد من الجهد لترجمة الأدب المكتوب باللغة العربية الذي تم إنتاجه في الفترات الأخيرة.
Keywords: الأدب -- الترجمة -- التبادل الثقافى